Temperature, Acidification, and Food Supply Interact to Negatively Affect the Growth and Survival of the Forage Fish, Menidia beryllina (Inland Silverside), and Cyprinodon variegatus (Sheepshead Minnow) - Gobler, Christopher J.; Merlo, Lucas R.; Morrell, Brooke K.; Griffith, Andrew W. (Frontiers in Marine Science, 2018)
Climate change processes are warming, acidifying, and promoting a reduction of plankton biomass within World oceans. While the effects of these stressors on marine fish have been studied individually, their combined and interactive impacts remain unclear. Here we present experiments investigating the interactive effects of increased pCO2, temperature, and food-limitation on the early life history traits of two species of marine schooling fish native to Northeast US estuaries, Menidia beryllina (inland silverside) and Cyprinodon variegatus (sheepshead minnow). While each stressor significantly altered hatching times, growth rates, and/or survival of fish, significant interactions between stressors resulted in impacts that could not have been predicted based upon exposures to individual stressors. Fish that were unaffected by high pCO2 when reared at ideal temperatures experienced significant declines in survivorship when exposed to elevated pCO2 at temperatures above or below their thermal optimum. Similarly, fish provided with less food were more vulnerable to elevated pCO2 than fish provided with adequate nutrition. These findings highlight the significance of incorporating multiple stressors in studies investigating the impacts of climate change stressors on marine life. Collectively, these results suggest that climate change stressors may interact to synergistically suppress the productivity of fisheries in coastal ecosystems and that these effects may intensify as climate changes continue.